Constructing DNA Codes with Larger Distance from Quaternary Words - Pradipta, Benediktus Panji; Puspita, Nikken Prima (Department of Mathematics, Universitas Negeri Gorontalo, 2025)
In this work, we propose a novel method to construct DNA codes from quaternary words. The method uses permutation groups that act in the set 1, 2, …, 4n, representing the coordinate and coordinate value of quaternary words. The DNA code is obtained by finding a clique of the construction graph and mapping it using the bijective map 0 → A, 1 → C, 2 → T, 3 → G. We present a new approach to construct DNA codes with larger Hamming distance and reverse-complement distance compared to previously obtained DNA codes. This is achieved by using a modified construction graph tailored to the desired distance parameter. As a result, we can refine a DNA code to have improved Hamming distance and reverse-complement distance while maintaining the fixed GC-content constraint. This method simplifies the search for DNA codes with large distance parameters.